Osteología DE Paralonchurus peruanus “suco” proveniente de la caleta de Huanchaco, La Libertad. - Cuyas Vera, Oscar David (2016)
The morphological study of bone elements is a valuable tool for taxonomy, which has allowed the definition of large groups of vertebrates as well as the description, identification and comparison at the level of families in fish. The objective of the present work is aimed at the identification and description of each one of the bony structures that make up the skeleton of Paralonchurus peruanus "suco". It was collected 3 specimens that were obtained of the catches of fishing in Huanchaco (Trujillo - Perú) and techniques were used for dismantling of fish in fresh for adult specimens. This species, from the point of view of the morphology of bone, is characterized by having in the neurocráneo two bumps and the spine consists of twenty seven vertebrae and presents bony bumps in the caudal vertebrae._x000D_ Keywords: Fish, Neurocranium, Osteology, Caudal vertebrae.